THE DIGGING-EST DOG I can read all by myself - PERKINS, AL (HARPERCOLLINS CHILREN'S BOOKS HONG KONG, 2006)
A dog can't be a dog in a pet shop. They can't run, they can't play, and they most definitely can't dig! This book is about a dog named Duke who desperately wants to get out of the pet shop--off of the "hard floor of stone". One day, a boy named Sam, saw him in the shop. He knew that a dog couldn't be a dog in a place like that! He took Duke back to his farm and made him feel at home. Sam introduced Duke to other dogs who liked to dig. Duke had never dug before, and just couldn't get the hand of it. Both Duke and Sam were very sad that Duke couldn't fit in with the other dogs. The next morning Duke learns to dig, but takes his new gift a little too far. He has to redeem himself by fixing his mistakes, and then finally finds his place on the farm with the other dogs
Shelving location "J"